Hanging by a thread : cotton, globalization, and poverty in Africa - Moseley, William G.; Gray, Leslie (Research in international studies. Global and comparative studies series, 2008)
The textile industry was one of the first manufacturing activities to become organized globally, as mechanized production in Europe used cotton from the various colonies. Africa, the least developed of the world's major regions, is now increasingly engaged in the production of this crop for the global market, and debates about the pros and cons of this trend have intensified. Hanging by a Thread: Cotton, Globalization, and Poverty in Africa illuminates the connections between Africa and the global economy. The editors offer a compelling set of linked studies that detail on.